Priming of Frames and Slots in Bilingual Children’s Code-Mixing: A Usage-Based Approach - Quick, Antje Endesfelder; Gaskins, Dorota; Frick, Maria (Frontiers in Psychology, 2021)
This paper investigates the role of direct input in the code-mixing of three bilingual children aged two to four years acquiring English as one language, and either German, Polish, or Finnish as the other. From a Usage-Based perspective, it is assumed that early children’s utterances are item-based and that they contain many lexically fixed patterns. To account for such patterns, the traceback method has been developed to test the hypothesis that children’s utterances are constructed on the basis of a limited inventory of chunks and frame-and-slot patterns. We apply this method to the code-mixed utterances, suggesting that much of the code-mixing occurs within frame-and-slot patterns, such as Was ist X? as in Was ist breakfast muesli? ‘What is breakfast muesli?’. We further analyzed each code-mixed utterance in terms of priming. Our findings suggest that much of the early code-mixing is based on concrete lexically fixed patterns which are subject to input occurring in immediately prior speech, either the child’s own or that of her caregivers.